Enhancing Critical Thinking in Mathematics through Android-Based Multimedia and PjBL-STEM - Kenny Candra Pradana; Sri Hastuti Noer; Sugeng Sutiarso (CV FOUNDAE, 2025)
Mastery of mathematics is essential for developing critical thinking skills; however, many students still struggle in this area. This study evaluated the effectiveness of Android-based interactive multimedia, MatHub: Pattern8 Edition, in enhancing critical thinking within PjBL using a STEM approach. The research took place at SMP Negeri 4 Bandar Lampung in the 2024/2025 academic year, employing a quantitative approach with a Pretest-Posttest Control Group Design. Using cluster random sampling, class VIIIC with 32 students was assigned as the experimental group, while class VIIIF with 33 students served as the control group. Data collection techniques included questionnaires, interviews, critical thinking assessments, observation checklists, and supporting documentation. The results showed a significant improvement in critical thinking skills among students using MatHub compared to those applying discovery learning without multimedia. Overall, integrating MatHub in PjBL-STEM improved learning quality, motivation, and student participation, offering an effective alternative for enhancing mathematical thinking